Aktivitas Antibakteri Sabun Cuci Tangan yang Mengandung Ekstrak Metanol Rumput Laut Eucheuma spinosum (Antibacterial Activity Test of Eucheuma spinosum Methanol Extract Hand Wash) - Nur Illiyyin Akib; Mariani Triwatami; Andi Eka Purnama Putri (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2019)
Background: Eucheuma spinosum seaweed contain flavonoid, triterpenoid, alkaloids and polyphenol which has been widely used in antibacterial activity. Purpose(s):The aim of the research are to determine antibacterial activities of metanol extracts of E. spinosum against Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 25922; to formulate hand wash of seaweed of methanol extract E. spinosum that has antibacterial activity and has physical and chemical stability. Methods: Seaweed E.spinosum methanol extract was derived by maceration method. Antibacterial activities of the extract were tested by liquid dilution and solid dilution method. Hand wash was formulated by mechanical dissolved methods. Antibacterial activity of hand wash were tested by liquid dilution and solid dilution method. Physical and chemical stabilities were conducted by cycling test. Results:. These were showed through minimum inhibitory concentration (MIC) of ethanol extracts of E. spinosum against S. aureus ATCC 25923 at concentrations of 6% and E. coli ATCC 25922 at concentrations of 6%. The minimum bactericidal concentration (MBC) of ethanol extracts of E. spinosum against S. aureus ATCC 25923 at concentrations of 8% and E. coli ATCC 25922 at concentrations of 8%. Formulation of hand wash seaweed E. spinosum methanol extract at concentrations of 8% and 10%. The test of stabilities results of hand wash changes were organoleptic, viscosity, pH, and foaming ability were accordance to qualified standard. The antibacterial activity of hand wash contains seaweed E. spinosum methanol extract at concentration of  8% and 10% have bactericidal activity againts S. aureus ATCC 25923 and E. coli ATCC 25922. Conclusion: Overall, these results suggested that formula of hand wash contains E. spinosum metanol extracts have antibacterial properties against S. aureus ATCC 25923 and E. coli ATCC 25922.Keywords: antibacterial, Eucheuma spinosum, hand wash, physical and chemical stability Latar Belakang: Rumput laut Eucheuma spinosum mengandung flavonoid, triterpenoid, alkaloid, dan polifenol yang memiliki aktivitas antibakteri. Tujuan: Penelitian ini bertujuan mengetahui aktivitas antibakteri ekstrak metanol E. spinosum terhadap Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 25922; membuat sediaan sabun cuci tangan dari ekstrak metanol E. spinosum yang memiliki aktivitas antibakteri dan stabil secara fisika dan kimia. Metode: Ekstrak metanol E. spinosum diperoleh dengan metode maserasi. Uji aktivitas antibakteri ekstrak dilakukan dengan metode dilusi cair dan dilusi padat. Sabun cuci tangan diformulasi dengan metode pencampuran mekanik. Uji aktivitas antibakteri sabun cuci tangan dilakukan dengan metode dilusi cair dan dilusi padat. Uji stabilitas fisika kimia dilakukan dengan metodecycling test. Hasil: Konsentrsi Hambat Minimum (KHM) ekstrak metanol E. spinosum terhadap S. aureus ATCC 25923 adalah 6% dan terhadap E. coli ATCC 25922 adalah 8%. Ekstrak metanol E. spinosum dapat diformulasi menjadi sabun cuci tangan dengan konsentrasi 8% dan 10%. Uji stabilitas menunjukkan bahwa perubahan organoleptik, viskositas, pH, dan kemampuan membentuk busa masih berada dalam nilai yang dipersyaratkan. Uji aktivitas antibakteri sabun cuci tangan yang mengandung ekstrak metanol E. spinosum dengan konsentrasi 8% dan 10% memiliki aktivitas antibakteri terhadap ATCC 25923 and E. coli ATCC 25922. Simpulan: Formula sabu cuci tangan yang mengandung ekstrak metanol E. spinosum memiliki aktivitas antibakteri terhadap ATCC 25923 and E. coli ATCC 25922.Kata kunci: antibakteri, Eucheuma spinosum, sabun cuci tangan, stabilitas fisika kimia